NIKMAT KEMERDEKAAN DAN CARA MENSYUKURINYA DALAM TINJUAN AL-QUR’AN DAN HADITS - Shodiq Ahmad, Mohammad (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2022)
In this August, the Indonesian people are commemorating and celebrating their 77th Independence Day (HUT). However, humans in responding to these favors there are those who deny and do not want to admit it. And there are also those who have acknowledged and are grateful, but they are still wrong in expressing their gratitude, and then there are also many people who abuse the grace and love of Allah SWT. The presence of this research aims to provide awareness to Muslims, in particular, and to mankind in general, that every gift of pleasure they get must be grateful for, and should not be disapproved of. In addition, this study also aims to provide guidelines, as well as instructions for Muslims how to express their gratitude for the blessings they have received from Allah, the Most Gracious and Most Merciful. The methodology used in this research is library research, namely by collecting data, including verses related to the theme of gratitude, along with several books of interpretation. So that the understanding of the data is able to inspire the message and its value, so that it can be applied to the context of the pleasure of independence. The results of this study indicate that there are many residents who think that the Indonesian Independence Day is a fun activity and a moment of mere fun. This is evidenced by the many events and activities that are almost filled with joy, and even partying. Therefore, the feeling of joy which is an expression of gratitude requires direction and guidance so that all forms of joy are directed to gratitude which has the value of worship, and can produce rewards that can be harvested later in the hereafter.